Visual dominance of the congruency sequence effect in a cross-modal context - Tang, Xiaoyu; Zhang, Xi; Wang, Tingting; Yu, Hongtao; Wang, Aijun; Zhang, Ming (Frontiers in Psychology, 2024)
The congruency sequence effect (CSE) refers to the reduction in the congruency effect in the current trial after an incongruent trial compared with a congruent trial. Although previous studies widely suggested that CSE was observed only in the modality repeat condition, few studies have reported that CSE could also appear in the modality switch condition. However, it remains unclear whether these conflicting findings were caused by partial repetition effects under modality transition conditions. To address this issue, Experiment 1 controlled for partial repetition effects by ensuring that the modality relationships in both the repetition and switch conditions were either fully congruent or incongruent. The results revealed significant CSE only under the modality repetition condition. In particular, a larger CSE was observed in visual–auditory (VA) repetition than in auditory–visual (AV) repetition, indicating that modality asymmetry might affect the CSE by inducing the priming effect. Thus, Experiment 2 concurrently presented visual and auditory stimuli to eliminate priming effects and further validated CSE differences between auditory and visual modalities. The results revealed that the CSE was significantly greater under the VA condition than under the AV condition and confirmed that the visual modality played a dominant role in the CSE, as visual information is prioritized in processing and ultimately reduces the congruency effect in the next trial. Overall, the present study provides evidence for the specificity of CSE under modality repetition conditions by excluding partial repetition effects and further underscores the critical role of visual dominance in cross-modal CSE.